Distribución bioclimática de plantas medicinales y sus principios activos en el Departamento de Cajamarca (Perú). - Galán-de-Mera, A.G. (2019)
This work presents a distribution of medicinal plants and active substances from Cajamarca Department (Peru) under a bioclimatic criterion. The results show that 108 medicinal plants are spread among five bioclimatic belts: infratropical, thermotropical, mesotropical, supratropical and orotropical. As a statistical analysis shows (non-metric multidimensional scaling, MDS), most of them are concentrated in the mesotropical belt and a subhumid precipitation range. In addition a canonical correspondence analysis (CCA), using the altitude (m), the thermicity index (It) and annual precipitation (P) as environmental variables, indicates how active substances are also distributed with tendencies of them, showing phenolic substances and essential oils as mesotropical products, and complex alkaloids to the highest It values, while simple alkaloids to the lowest It values. Most of these molecular compounds are generated under the highest values of the subhumid and humid precipitation intervals. This bioclimatic method can led us to find new medicinal plants and active molecules.